Premature ovarian insufficiency and chance of pregnancy after childhood cancer: A population-based study (the Fex-Can study) - Haavisto Anu; Wettergren Lena; Lampic Claudia; Lähteenmäki Päivi M; Jahnukainen Kirsi (WILEY, 2025)
Endocrine complications are a common late effect after childhood cancer. Our study assessed the prevalence and predictors of premature ovarian insufficiency (POI) and prospects of pregnancy in young female survivors. This nationwide study combined registry and survey data for female childhood cancer survivors aged 19 to 40 years, identified through the National Quality Registry for Childhood Cancer in Sweden. Of 1989 approached young women, 1333 (67%) participated by completing a survey. Median age at diagnosis 1981 to 2017 was 6 (range 0-17) and at study 28 (19-40) years. There were two indicators of POI, induced puberty reported in 5.3% and estrogen replacement therapy (ERT) in 9.3% at assessment. In separate logistic regression analyses (P < .001), induced puberty and ERT were significantly predicted by hematopoietic stem cell transplantation (HSCT), abdominal irradiation, central nervous system irradiation and chemotherapy. ERT was also associated with older age at diagnosis. Of the 626 women (48% of responders) who had tried to become pregnant, 25% had undergone fertility investigations and 72% reported having a biological child. Treatment with HSCT was associated with 5.4 times the odds of needing fertility investigations (P < .001). Having a biological child was associated with non-HSCT treatment, but also with ever having had a partner and older age at the time of study (all P < .001). In conclusion, the majority of those female childhood cancer survivors who had tried to conceive were able to successfully give birth. However, a small identifiable group of female survivors are at risk of subfertility and early menopause.